2017
DOI: 10.1155/2017/1592598
|View full text |Cite
|
Sign up to set email alerts
|

FRAX® Fracture Risks Are Associated with Coronary Artery Calcification Score

Abstract: Purpose To examine the association between fracture risk assessment tool (FRAX) scores and coronary artery calcification (CAC) score in adults. Methods The medical records of 81 adults who underwent both coronary computed tomography and bone mineral density (BMD) studies in a package during their health exams were reviewed at a regional hospital in Southern Taiwan. Data collected included health history, anthropomorphic characteristics, clinical laboratory results, and BMD. Fracture risk was determined using F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In line with an earlier review [9], we found significant independent associations between BA, prevalent VFs, and high Agatston score. An association between VFs and Agatston score is consistent with the reported correlation of FRAX-estimated risk of hip fracture or major osteoporotic fracture with CAC score [38]. Some linking mechanisms have been proposed, such as an association between micro-and macro-vessel damage and altered microarchitectural indices in the radius [39], or between decreased vascular flow in the lower extremities and increased rate of bone loss at the hip and calcaneus in older women [40].…”
Section: Discussionsupporting
confidence: 80%
“…In line with an earlier review [9], we found significant independent associations between BA, prevalent VFs, and high Agatston score. An association between VFs and Agatston score is consistent with the reported correlation of FRAX-estimated risk of hip fracture or major osteoporotic fracture with CAC score [38]. Some linking mechanisms have been proposed, such as an association between micro-and macro-vessel damage and altered microarchitectural indices in the radius [39], or between decreased vascular flow in the lower extremities and increased rate of bone loss at the hip and calcaneus in older women [40].…”
Section: Discussionsupporting
confidence: 80%
“…In the study, their correlation between BMD and CAC score was more significant for the femur area than for the lumbar spine. In another study analyzing FRAX ® and CAC, only the right femoral neck T-score and left total hip T-score showed a significantly inverse relationship with the CAC score [ 34 ].…”
Section: B One Mineral Density and Cardiovascular Disease/cmentioning
confidence: 99%
“…Fracture risk, rather than mere BMD, was significantly positively correlated with CAC scores. This correlation is probably because, in addition to the BMD value, the calculation of major osteoporotic fracture and hip fracture risk takes into account other fracture risk factors [ 34 ].…”
Section: Frax ® and Cardiovascular Disease/coronmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial calcification is one of the independent predictor factors of vascular morbidity and mortality in the elderly population [ 5 ]. It has been reported that if there is a significant association between fragility fractures and vascular calcification, it can be explained by the fact that these vessels and bones are a dynamic process related to the physiological microenvironment [ 6 ]. Local and systemic osteogenic factors that may be released from calcified atherosclerotic lesions may affect bone homeostasis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%